Effects of imipramine on cancer patients over-expressing Fascin1; description of the HITCLIF clinical trial - Asensi-Cantó, Antonio; Rodríguez-Braun, Edith; Beltrán-Videla, Asunción; Hurtado, Ana María; Conesa-Zamora, Pablo (Frontiers in Oncology, 2023)
Background Tumor invasion and metastasis are responsible for the majority of cancer-related deaths. The identification of molecules involved in these processes is crucial to design effective treatments that can halt the progression of cancer. To spread and metastasize, tumor cells must restructure their cytoskeleton and emit protrusions. A key molecule in this process of creating these invading structures is Fascin1, the main protein involved in the formation of actin cytoskeleton bundles and a consistent marker of bad prognosis in several types of cancer. Recent studies have shown that imipramine, an FDA- and EMA-approved antidepressant, can block Fascin1and prevent the formation of actin bundles, making it a promising candidate for the treatment of Fascin1-expressing cancers. As a result, a clinical trial will be conducted to assess the efficacy of imipramine being the first experimental clinical study selecting patients based on Fascin1 expression. Methods The HITCLIF trial is a multicenter, double-blind, placebo-controlled, randomized and non-commercial phase II clinical trial conducted in parallel groups to evaluate the effectiveness of the tricyclic antidepressant imipramine as anti-invasive agent in the treatment of localized colon, rectal and triple negative breast cancer patients with overexpression of Fascin1. Eligible patients will be randomly assigned, in a 1:1 ratio, to receive imipramine or placebo. Patients will be stratified into 2 groups according to whether administration of imipramine is concomitant with neoadjuvant chemotherapy regimen. Group A will receive imipramine alone without neoadjuvant chemotherapy, while Group B will receive imipramine treatment along with the standard neoadjuvant chemotherapy regimen. The primary endpoint of the trial is the grade of alteration in the prognostic histopathological features at invasive margins (tumor budding, cytoplasmic pseudo-fragments, tumor growth pattern, and peritumoral lymphocytic infiltration). Discussion Fascin1 is an interesting therapeutical target as it plays a causative role in the invasion and metastasis of cancer cells. Moreover, its expression is virtually absent in normal epithelia but highly expressed in cancer with bad prognosis. In silico, in vitro and in vivo studies by our group have demonstrated that the antidepressant imipramine has Fascin1-dependant anti-invasive and anti-metastatic effects in colorectal cancer cells. Now we are recruiting patients in a clinical trial based on Fascin1 over-expression in which administration of imipramine will be carried out during the period between the diagnosis biopsy and surgical resection to explore the drug effects on tumor invasive front. Clinical trial registration https:///www.clinicaltrialsregister.eu/ctr-search/trial/2021-001328-17/ES, identifier 2021-001328-17.